Structural and Thermal Characterization of Castor Oil Based Unsaturated Polyester Resin - Chowdhury, A.; Singh, S.K.; Anthony, P. (Asian Journal of Chemistry, 2020)
In the present study, unsaturated polyester resins based on castor oil was synthesized. Structure elucidation of the synthesized unsaturated polyester resin was done by FTIR and 1H NMR spectroscopy. Thermogravimetric analysis was used to evaluate the thermal stability of cured unsaturated polyester resin. Thermogram plot was further utilized to calculate various other parameters such as statistic heat-resistant index (Ts) and the integral procedural decomposition temperature (IPDT). Comparable properties with respect to commercial resins were reported for the synthesized polymers.